Haematological and Metabolic Profile Test of Subclinical Mastitis Affected Cross Bred Cattle - Lakshmi, R.; Vijayakaran, K.; Kaarthick, D. T.; Ramkumar, P. K.; Karthika, K.; Saravanan, M.; Arunmozhi, N.; Vijayarajan, A. (International Journal of Bio-resource and Stress Management, 2024)
The current research was conducted during May–October, 2023 aimed to assess the haemato-biochemical parameters in cattle affected with S. aureus affected subclinical mastitis. Mastitis in dairy cattle is the persistent, inflammatory reaction of the udder tissue. Financial losses due to mastitis occur in the case of both sub-clinically and clinically affected animals. Sub-clinical mastitis exhibits no clinical signs and mostly remains unnoticed by the farmer and can be detected if specific tests are performed in milk samples. Sub-clinical mastitis has an erosive effect on the economy of dairy farmers as it effect directly on the milk quality and quantity. In India prevalence of sub-clinical mastitis was found to be more in cows when compared to clinical mastitis. Blood samples were collected from the jugular vein of 10 healthy and 10 subclinical mastitis affected cattle. Blood samples were analyzed for Hb, PCV, TEC, TLC, while serum samples were examined for ALT, AST, ALP, Glucose, Total protein, Albumin, Cholesterol and Calcium. Haematology report showed significantly (p<0.01) decrease in Hb, PCV and TEC in subclinical affected cattle when compared to healthy animals. TLC was significantly increased in (p<0.01) subclinical affected animal than healthy animal. Biochemical estimate revealed significantly (p<0.05) higher average values of AST, ALP and Ca in subclinical mastitis affected animals compared to healthy animals. Glucose, total protein, albumin, cholesterol and ALT levels are significantly (p<0.05) decrease in subclinical mastitis affected animals when compared to healthy cows. Haemato-biochemical parameters can be used as important for pathological state of subclinical mastitis animals.